Effect of Learning Management toward using Program Simulation Instructional Media for Injection on Satisfaction of 2nd year nursing students. - Winitchai, Natchira (NU Journal of Nursing and Health Sciences, 2021)
This research is a Quasi-experimental One Group Posttest only Design aimed to explore Effect of Learning Management toward using Program Simulation Instructional Media for Injection on Satisfaction of 2nd year nursing students were enrolled studied in Fundamental Nursing Laboratory course. The sample of this study consist of 72 students. Data was collected by using personal data questionnaires and the satisfaction towards the program. The reliability of Cronbach’s Alpha Coefficient was 0.94. Data analysis was based on descriptive statistics. According to the findings, satisfaction toward using Program Simulation Instructional Media for Injection was at high level (x̄ = 4.04, S.D.=1.43). Moreover, satisfaction for the content meets the needs of the program user also at high level (x̄ = 4.19, S.D.=0.93), clarity of the media according to the function of the program also at high level (x̄ = 3.99, S.D.=1.42) and easy of use of the program also at high level (x̄ = 3.83, S.D.=0.66). The results of this study indicated that management of teaching and learning of Fundamental Nursing Laboratory course current nursing students should use simulation technology to enable students to practice their skills. Review the correct principles in the laboratory for confidence to apply the knowledge and skills to practice in order to prevent adverse events.